PENGUATAN PENYALURAN KPR DI INDONESIA DALAM MEMENUHI KEBUTUHAN BACKLOG (Studi pada Bank Umum Konvensional Periode 2013-2015) - Shoimatul Fitria; Erna Dwi Astutik (Fokus Bisnis : Media Pengkajian Manajemen dan Akuntansi, 2017)
The condition of economic fundamentals declining with the marked economic growththat only reached 4.51% and the value of rupiah that penetrated Rp13.000,00 make theprimary housing finance market (PPPP) in Indonesia become sluggish. This makes HousingLoans (KPR) declining. In addition, the policy of maintaining the BI rate at 7% and the 30%loan to value (LTV) policy also makes PPPP in Indonesia decreasingThe samples used were selected by purposive sampling method with some criterias. Thesamples in this study are 36 Conventional Commercial Banks in Indonesia that providehousing loan in period 2013-2015. The data used in this study were obtained from theBanking Annual Report 2013-2015. This study used Multiple Linear Regression Analysisthat includes classic assumption test, coefficient of determination test (RÂ²), F statistic test,and t statistic test.The result of this research showed that DPK and NPL significantly positive influence toTotal of Housing Loans, housing loan interest rates has negative significant effect to Totalof Housing Loans. Whereas the determination of the test based on the research model thatcan explain the dependent variable well enough that it can be seen from the R Square valueof 0,47. This means that the ability of model prediction was 47% while the remaining 53%influenced by other variables outside the research.Keywords: third party fund, housing loan interest rates, non performing loan, housing loan